The Primacy of Semiosis : An Ontology of Relations - Bains, Paul (Book collections on Project MUSE., 2006)
"The Primacy of Semiosis provides a semiotic that subverts the opposition between realism and idealism, one in which what have been called 'nature' and 'culture' interpenetrate in an expanding collective of human and nonhuman. Bains's work promises to be a touchstone for semiotic discussion for years to come."--Jacket.